Redescription of Pomatostegus stellatus (Abildgaard, 1789) and P. kroyeri Mörch, 1863 (Polychaeta: Serpulidae) from the Tropical American coasts - Sánchez-Ovando, J. Pablo; Bastida-Zavala, J. Rolando (Zootaxa, 2021)
Pomatostegus Schmarda, 1861 is a serpulid genus with three recognized species, mostly from tropical waters. Pomatostegus stellatus (Abildgaard, 1789), was described from the Caribbean Sea, and has been widely recorded in the Pacific and Indian oceans; P. kroyeri Mörch, 1863 was described from Puntarenas, Costa Rica; however, most records from the Tropical Eastern Pacific were referred to P. stellatus. In this work, the two species are redescribed using morphological characters. The main differences are in the shape of the Spirobranchus-type collar chaetae, opercular plate shape and the number of “free” circlets of spines without accompanying of opercular plates. Comments about characters of P. actinoceras Mörch, 1863, described from Philippines, and an identification key for the three species, are included.